Meta-Analysis of Financial Literacy Antecedents Variables : A Case on Millenials Generation - Riani, Lilia Pasca; Fikri, Aula Ahmad Hafidh Saiful; Sholeh, Maimun; Supriyanto, Supriyanto (Universitas Nusantara PGRI Kediri, 2023)
Research aim : This research is a confirmation study using antecedent variables from the construct of financial literacy to be proven to have a significant relationship if applied to the millennial generation as research subjects. Design/Methode/Approach : Systematic Literature Review Research Finding : As many as 30 antecedent variables were obtained that affect the financial literacy of the millennial generation Theoretical contribution/Originality : The research subjects in the form of relevant research articles were taken through the Google Scholar, Elsevier, Emerald, Garuda portal, etc. as many as 214 articles were detected through the keywords of financial literacy, financial knowledge, retirement, financial decisions, financial management, and financial welfare. The articles were then extracted into only 60 research articles. Of these 60 articles, correlational meta-analysis was carried out. The results of the meta-analysis show that there are 30 antecedent variables that affect the financial literacy of the millennial generation. Practitionel/Policy implication : The results of this study will help policy makers to fill the missing gap between financial literacy programs and the confidence to undertake entrepreneurial ventures. Research limitation : The limitation of this research is that the source of published articles has not reached Scopus indexed journals. so that the possibility of bias in the results of research on each article is still relatively large